Training of caregiver for home care management of stroke survivor at low resource setting (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
This study was carried out to see whether caregiver training to attendees during hospital stay can better address the stroke survivor at home. In total 119 admitted patients hailed from remote villages were randomly selected from a private neurology hospital in Dhaka and were divided into two groups. One group had caregiver training and another group without training. All the patients were assessed for Barthel index at discharge and after 2 months. Barthel index in Group A during discharge was 6.2 ± 4.0 and at follow-up was 56.4 ± 9.0. The index in Group B was 4.9 ± 4 during discharge and 28.2 ± 7.8 at follow-up. Results were statistically significant. In conclusion, this study reveals the positive effects of caregiver training in the post-acute care management of stroke survivors at home.